Ліричні й епічні аспекти поетики кримськотатарської народної пісні «Он биринджи айларда горюнди дагълар» - Гуменюк, О.М. (Культура народов Причерноморья, 2013)
У статті осягається художній світ кримськотатарської фольклорної пісні, насамперед
така риса її поетики як поєднання ліричних та епічних аспектів. Дослідниця відзначає здобутки
фольклористів у царині фіксації й вивчення кримськотатарської народної пісні, наголошує на значенні
ґрунтовних фольклористичних збірників Я. Шерфедінова, Іл. Бахшиша, Ф. Алієва, які є надійною
джерельною базою вивчення пісенного фольклору кримських татар.
Основна увага приділяється тематичним мотивам та особливостям поетики пісні «Он биринджи
айларда горюнди дагълар» («На одинадцятий місяць прозирнули гори»). Проникливе осягнення людських
печалей і радостей; туга розлуки з рідною землею й коханою дівчиною; передача широкої гами почуттів,
тонких настроєвих відтінків, неабияке інтонаційне багатство; мальовнича метафоричність та
символічна сконденсованість лаконічної образності; динамічний розвиток ліричного сюжету, за яким
виразно вгадуються обриси сюжету фабульно-оповідного; стрункість та вигадливість композиції;
система експресивних повторів, яка посилює орнаментальність і чітку злагодженість викладу;
вишукана звукова й ритмічна організація – такі провідні особливості поетичного світу цієї
кримськотатарської народної пісні.
Ключові слова: кримськотатарський фольклор, пісня, тематичний мотив, поетика, ліричні й епічні
аспекти. В статье постигается художественный мир крымскотатарской фольклорной песни,
прежде всего такая черта ее поэтики как сочетание лирических и эпических аспектов.
Исследовательница рассматривает достижения фольклористов в сфере фиксации и изучения
крымскотатарской народной песни, подчеркивает значение фундаментальных фольклористических
сборников Я. Шерфединова, Ил. Бахшыша, Ф. Алиева, являющихся надежной основой изучения песенного
фольклора крымских татар. Основное внимание уделяется тематическим мотивам и особенностям
поэтики песни «Он биринджи айларда горюнди дагълар» («Лишь на одиннадцатый месяц показались
горы»).
Проникновенное постижение людских печалей и радостей, грусть разлуки с родной землею и любимой
девушкой, передача широкой гаммы чувств, тонких оттенков настроения превалируют в этом
фольклорном произведении. Интонационное богатство, живописная метафоричность и
сконденсированная символика лаконичной образности, динамическое развитие лирического сюжета, за
которым явственно угадываются черты сюжета фабульного, стройность и изысканность композиции,
система экспрессивных повторов, усиливающая орнаментальность и четкую слаженность изложения,
эффектная звуковая и ритмическая организация – такие основные особенности поэтического мира
этой крымскотатарской народной песни.
Ключевые слова: крымскотатарский фольклор, песня, тематический мотив, поэтика, лирические и
эпические аспекты. The artistic world of the folk song by Crimean Tatars, first of all such feature of its poetic as unity of
lyrical and epic aspects is investigated in this work. The authoress of the investigation accentuates the
importance of lyric song in the genre system of the national folklore. The exploreress considers the acquisitions
by the folklorists in the branch of the fixation and studying of the Crimean folk sons, particularly the works by
Alexey Olesnytsky, Arkady Konchevsky, Murtaza Velidzhanov and others. She emphasizes the importance of the
fundamental collection by Yahya Sherfedinov, which was edited in Tashkent in 1979, also the anthologies by
Fevzi Aliyev, Ilyas Bakhshysh, which were appeared in Simferopol in 2001 and 2004. These works make up a
solid base for the studying of the song folklore by Crimean Tatars.
The authoress of the research pays a special attention on the thematic motives and poetic peculiarities of such
song as “On birincι aylarda gorüncι dağlar” (“The hills appeared only after eleven months”). She writes about
prevailing of sad motives in this song. But these sad motives do not produce any oppressive effect. Marked by
poetical grace, they conceal in themselves a great charge of the catharsis and have a therapeutic effect. The fare
unknown creators of this song probably felt this effect when they had poured out their troubles and grieves into
them. And now the singers and the hearers continue to feel it.
A penetrative comprehension of human sorrows and pleasures; a translation of a broad scale of feelings and of
slender tins of mood; richness of different tonalities; picturesque metaphors and concentrated symbols in a
laconic figurative manner; a dynamic development of a lyric plot, where one can guess contours of a narrative
topic; slenderness and refinement of composition (successive, retrospective or mosaic); a system of expressive
reiterations, which reinforce an ornamental concord of exposition; an effective sound and rhythmic organization
– such are the main peculiarities of the poetic world of this folk song Crimean Tatars.
Key words: folklore by Crimean Tatars, song, thematic motive, poetics, lyrical and epic aspects.